ACTIVE LEARNING IN LETTER FORMATION: A METHODOLOGICAL APPROACH FOR A TEXTUAL LANGUAGE DISCIPLINE - Ferreira de Mello, Adriene; Marieli Pereira Caetano, Joane; Medeiros de Souza, Carlos Henrique (LINKSCIENCEPLACE, 2026)
The article discusses teacher education in Letters, specifically about the preparation for working with texts in the classroom, based on the research question: how can active methodologies contribute to the formative practices of the future Portuguese teacher in the field of Textual Linguistics (LT)? It is intended, in general, to analyze possible methodological paths for the active activities around the LT discipline. As specific objectives, we present a brief overview of the dilemmas and myths circumscribed to the practices of textual production; to discuss the applicability of active teaching methodologies (MA) as pedagogical alternatives; and, in the end, to suggest an active approach to LT discipline, through the use of technological resources: from teaching to evaluation. Methodologically, this is a qualitative research, whose theoretical support focuses on Passarelli (2012) and Pécora (1983) with his theoretical considerations on the conception of the text in the pedagogical dynamics; Schneider (2015) and Moran (2018) about MAs; and Dudeney, Hockly and Pegrum (2016) regarding digital literacy. This research is justified by the importance of promoting discussions about the practices related to the production of texts, in particular, the skills required by the LT discipline in teacher education in Literature.